The Use of Particles in Ngapak Bumiayu Language: A Study of Systemic Functional Linguistics - Atiq Aqiqotul Hasanah; Ilyas Daud (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2024)
This study explores the use of particles in Ngapak Bumiayu, a Javanese dialect spoken in Bumiayu, Brebes, Central Java, using Michael A.K. Halliday's Systemic Functional Linguistics theory. Data was collected from everyday conversations of native speakers using a descriptive analysis method. The identified particles—kok, lho, kok ya, toh, wis, and bar—each have unique roles in sentence structure and meaning. The ideational metafunction shows that these particles enrich the information in sentences. Without particles, sentences present straightforward facts, but with particles, they carry additional nuances that enhance the message. For the interpersonal metafunction, particle placement affects meaning. Kok can be in any sentence position, conveying surprise or emphasis. Lho emphasizes attention. Kok ya, typically at the beginning or middle, shows wonder and affirmation. Toh, usually at the end, indicates finality. Wis, in the middle or end, signifies completion or agreement. Bar indicates ongoing or recent actions. The textual metafunction highlights particles' role in maintaining text coherence and cohesion. They ensure consistency and continuity in discourse through repetition, serving as connectors (referential cohesion), and maintaining consistent meanings across contexts (lexical cohesion). These particles are essential for structuring and organizing information in sentences and conversations. These findings illustrate the significant role of particles in enhancing communication, structuring information, and providing nuanced meanings in the Ngapak Bumiayu language.